(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The Evolution of English Language Teaching (ELT) methodologies has been a dynamic narrative that highlights the continuous changes and transformation of language education. This article provides a comprehensive overview of the historical developments in ELT methodologies, from the traditional approaches to modern pedagogies, and discusses the impact of these changes on language acquisition.